Differences in visual reaction characteristics in national level cadet and junior female handball players - Markovic, S.; Valdevit, Z.; Bon, M.; Pavlovic, L.; Ivanovic, J.; Dopsaj, M. (Facta Universitatis: Series Physical Education and Sport, 2019)
This paper aims to define differences in Simple Visual Reaction Time (SVRT) and Reaction Time Variation (RTV), related to age and player position in Serbian female cadet and junior national handball team members. The method used in this research was laboratory testing. All data sampling was performed using specially designed testing software that recorded visual reaction time with 1 ms precision. SVRT was expressed in ms, and RTV was expressed as a coefficient of variation percentage value. The overall sample consisted of 34 players - 19 cadets and 15 juniors. Mean SVRT of 194.28±16.55 and 184.73±16.68 ms was determined in the subsamples of cadet and junior players, respectively. It was found that cadets have a mean RTV of 4.74±2.41% while juniors have a mean RTV of 7.90±3.70%. Results of the Factorial ANOVA have shown that there are no general, statistically significant, differences in SVRT in relation to age, player position, and interaction of these factors (p>0.05). Statistically significant difference in RTV on a general level was found in relation to age (F=9.752, p=0.005), while differences in relation to player position or combination of these factors were not statistically significant (p>0.05). Post hoc tests have shown partial differences in relation to player position. The method of mathematical modelling was used to define the statistical model of performance in relation to the given variables. The final form of the model explained 100% of the measured variance (AdjR2 = 1.000), which implies its absolute predictive potential considering the characteristics of the sample.